Enhancing drug solubility through competitive adsorption on silica nanosurfaces with ultrahigh silanol densities - Zhuo Xu; Changliang Zhu; Hongchuan Shen; Yuan Liu; Jiashen Tang; David A. Weitz; Lei Xu (Proceedings of the National Academy of Sciences, 2025)
We develop a technology based on competitive adsorption between drug molecules and water, specifically designed to address the critical issue of poor drug solubility. By specially engineering silica nanosurfaces with ultrahigh densities of silanol, we significantly enhance their affinity for both drug molecules and water, with a notably greater increase in water affinity. Such surfaces can effectively adsorb a variety of drug molecules under dry conditions. Upon exposure to water, these surfaces preferentially bind to water molecules, initiating a competitive adsorption process with the drug molecules. This competitive process turns water molecules from obstacles into catalysts for drug dissolution by actively displacing drug molecules from the surface, causing their rapid desorption and potentially enhancing their solubility by two to three orders of magnitude. The method is general, applicable to a wide array of drugs, stable for long-time storage, cost-effective, and scalable for mass production. Consequently, it has the potential to emerge as a next-generation platform for drug formulation and delivery.